PENGARUH UKURAN KOMITE AUDIT, KOMPLEKSITAS PERUSAHAAN, LIKUIDITAS DAN UKURAN KANTOR AKUNTAN PUBLIK TERHADAP AUDIT DELAY - Farandi Aditya DIlny, Adnan (2022)
This research aims to prove empirically the influence of size of audit committee, complexity, liquidity and size of public accounting firms against audit delay in property and real estate sector companies in the period 2018-2020. The research that uses secondary data to obtain the required data, namely annual reports and financial statements audited. In this study, the sample used was as many as 49 companies using purposive sampling techniques using established criteria. Techniques used n analyzing data are, regression model selection using STATA software version 16. Based on the results of analysis of the data that has been presented, it can be concluded that 1) Size of Audit Committee has no effect on Audit Delay; 2) Complexity has positively significant effect on Audit Delay; 3) Liquidity has no effect on Audit Delay; and 4) KAP Size has no effect on Audit Delay. Keyword: Size of Audit Committee, Complexity, Liquidity, and KAP Size